1999
DOI: 10.1038/7939
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of a fungal peroxidase

Abstract: The Coprinus cinereus (CiP) heme peroxidase was subjected to multiple rounds of directed evolution in an effort to produce a mutant suitable for use as a dye-transfer inhibitor in laundry detergent. The wild-type peroxidase is rapidly inactivated under laundry conditions due to the high pH (10.5), high temperature (50 degrees C), and high peroxide concentration (5-10 mM). Peroxidase mutants were initially generated using two parallel approaches: site-directed mutagenesis based on structure-function considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
165
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(170 citation statements)
references
References 19 publications
2
165
0
3
Order By: Relevance
“…In this respect, the CiP peroxidase promises to be a highly interesting biocatalyst. The enzyme is available on a large scale (from Novo Nordisk), and it has already been shown that mutants may be obtained via directed evolution techniques (53). This may also be the way to obtain an improved biocatalyst for application in epoxidation reactions.…”
Section: Conversions Of the Different Styrene Derivatives By Cip And Mpomentioning
confidence: 99%
“…In this respect, the CiP peroxidase promises to be a highly interesting biocatalyst. The enzyme is available on a large scale (from Novo Nordisk), and it has already been shown that mutants may be obtained via directed evolution techniques (53). This may also be the way to obtain an improved biocatalyst for application in epoxidation reactions.…”
Section: Conversions Of the Different Styrene Derivatives By Cip And Mpomentioning
confidence: 99%
“…Directed evolution experiments can indeed yield synthetic catalysts that are thermostable and active either at high (77) or low (78,79) temperatures. However, when random mutants of mesophilic and thermophilic enzymes were only screened for high activity at low temperatures during directed evolution (80)(81)(82)(83)(84)(85), the evolved enzymes generally display a concomitant reduced thermostability.…”
Section: Figmentioning
confidence: 99%
“…The heme peroxidase from Coprinus cinereus was subjected to multiple rounds of directed evolution in an effort to produce a mutant stable in laundry detergent conditions: pH 10.5 at 50ºC and 5-10 mM peroxide concentration [237]. Manually combining mutations from the site-directed and random approaches led to a mutant with 110 times the thermal stability and 2.8 times the oxidative stability of the wild-type enzyme.…”
Section: Evolved Enzymesmentioning
confidence: 99%